Foxo-mediated Bim transcription is dispensable for the apoptosis of hematopoietic cells that is mediated by this BH3-only protein - Herold, Marco J (European Molecular Biology Organization, 2013)
The BH3-only protein Bim is a critical initiator of apoptosis in hematopoietic cells. Bim is upregulated in response to growth factor withdrawal and in vitro studies have implicated the transcription factor Foxo3a as a critical inducer. To test the importance of this regulation in vivo, we generated mice with mutated Foxo-binding sites within the Bim promoters (Bim(ΔFoxo/ΔFoxo)). Contrary to Bim-deficient mice, Bim(ΔFoxo/ΔFoxo) mice had a normal hematopoietic system. Moreover, cytokine-dependent haematopoietic cells from Bim(ΔFoxo/ΔFoxo) and wt mice died at similar rates. These results indicate that regulation of Bim by Foxo transcription factors is not critical for the killing of hematopoietic cells.